PENGARUH DESENTRALISASI FISKAL TERHADAP PERTUMBUHAN EKONOMI DAERAH DI PULAU JAWA TAHUN 2017–2024 - Elang Agastha, Mochhans; Aulia Rahman, Yozi (Penerbit Lafadz Jaya, 2025)
Regional development disparities in Indonesia, particularly in Java Island which serves as the national economic hub, remain a major challenge in achieving inclusive economic growth. Fiscal inequality and differences in regional financial capacity require the implementation of effective fiscal decentralization policies. This study aims to examine the influence of fiscal decentralization instruments—General Allocation Fund, Special Allocation Fund, Revenue Sharing Fund, and Regional Own-Source Revenue—on economic growth across six provinces in Java Island during the period 2017 to 2024. The research applies a panel data regression method using the Pooled Least Square approach, with secondary data obtained from the Central Bureau of Statistics and the Directorate General of Fiscal Balance. The results reveal that Regional Own-Source Revenue has a positive and significant impact on economic growth, while the Special Allocation Fund exhibits a significant negative effect. The Revenue Sharing Fund shows a negative but statistically insignificant relationship, and the General Allocation Fund has no significant impact. Simultaneously, all four fiscal variables significantly influence regional economic growth. These findings suggest that the effectiveness of fiscal decentralization depends not only on the size of the transfers but more importantly on the strategic use of funds and the institutional capacity of local governments. Strengthening local fiscal independence and reformulating transfer schemes are crucial to achieving balanced regional development.